Telephone numbers, domain names, and ENUMbers. - McTaggart, C. (IEEE Communications magazine)
One of the biggest barriers to the development of public IP telephony services has been the lack of a universal addressing system. While IP-enabled devices have long been capable of originating phone and fax calls, it is difficult to "call" an IP device because they are hard to find. Internet Engineering Task Force (IETF) Request for Comments (RFC) 2916, "E.164 Number and DNS," seeks to solve this problem in a simple and perhaps unlikely way. Simple, in that the ENUM protocol converts existing telephone numbers into domain names.The designers of ENUM hope to foster a global megadirectory of communications users who can be reached in any number of ways by means of only one number. While theoretically any character space could be standardized in an attempt to create a universal addressing scheme, ENUM explicitly adopts telephone numbers, presumably to take advantage of their global user acceptance and mature infrastructure. This choice adds a significant public policy dimension to the story. Far from being benign and boring, telephone numbers can present significant communications policy issues, and are regulated both domestically and internationally. The top level of this hierarchy is defined by International Telecommunication Union-Telecommunication Standardization Sector (ITU-T) Recommendation E.164